The 100, homecoming - Kass Morgan (London : Hodder & Stoughton, 2016)
"Weeks after landing on Earth, the Hundred have managed to create a sense of order amidst their wild, chaotic surroundings. But their delicate balance comes crashing downwith the arrival of new dropships from space. These new arrivals are the lucky ones - back on the Colony, the oxygenis almost gone... It's time for the Hundred to come togetherand fight for the freedom they've found on Earth, or risk losing everything - and everyone - they love"--Publisher.
Young Adult.